Municipal garden shovel - YIN CHUANSONG (2018)
The utility model discloses a municipal garden shovel, including shovel head and handle, the shovel head shovels the body including the first shovel body and second, and the second shovel body is whole to be the U -shaped, has the caulking groove on its inside wall, have on the lateral wall of the first shovel body with caulking groove complex fillet, the top of the first shovel body is provided with first lock seat, and the top of the second shovel body is provided with second lock seat, install on the second lock seat and be used for the locking subassembly of first lock seat with the locking of second lock seat, the locking subassembly includes latch fitting and spring, the top of second lock seat is provided with the mounting groove, and the latch fitting is located the mounting groove, and one side of the first lock seat of its orientation is provided with at least one inserted bar, run through on the lateral wall of mounting groove and be provided with the first lock seat of at least one slot that suppl